2016
DOI: 10.1161/circep.113.003638
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix–Mediated Maturation of Human Pluripotent Stem Cell–Derived Cardiac Monolayer Structure and Electrophysiological Function

Abstract: Background Human pluripotent stem cell-derived cardiomyocyte (hPSC-CMs) monolayers generated to date display an immature embryonic-like functional and structural phenotype that limits their utility for research and cardiac regeneration. In particular, the electrophysiological function of hPSC-CM monolayers and bioengineered constructs used to date are characterized by slow electrical impulse propagation velocity and immature action potential profiles. Methods and Results Here we have identified an optimal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
275
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 238 publications
(303 citation statements)
references
References 53 publications
25
275
2
1
Order By: Relevance
“…The low contraction amplitude of cardiac organoids is possibly due to the increased extracellular matrix components (e.g., collagen) and interstitial cell types, resulting in a denser/stiffer construct that creates an increased load for cardiomyocyte contraction. This was supported by the improved contractile structure and gene profile in cardiac organoids despite low contraction amplitude, highlighting the importance of the multicellular and matrix environment for hiPSC-CM maturation and ventricular lineage specification seen by others (26, 81). It is worth noting that the observed relationship between cardiomyocyte function and changes in cellular/ECM components is equally important to cardiac development and maturation as it is to cardiac pathophysiology, such as in chronic cardiac fibrosis (82, 83).…”
Section: Resultssupporting
confidence: 63%
“…The low contraction amplitude of cardiac organoids is possibly due to the increased extracellular matrix components (e.g., collagen) and interstitial cell types, resulting in a denser/stiffer construct that creates an increased load for cardiomyocyte contraction. This was supported by the improved contractile structure and gene profile in cardiac organoids despite low contraction amplitude, highlighting the importance of the multicellular and matrix environment for hiPSC-CM maturation and ventricular lineage specification seen by others (26, 81). It is worth noting that the observed relationship between cardiomyocyte function and changes in cellular/ECM components is equally important to cardiac development and maturation as it is to cardiac pathophysiology, such as in chronic cardiac fibrosis (82, 83).…”
Section: Resultssupporting
confidence: 63%
“…Tbx20, either WT or p.R311C, did not modify the voltage dependence of Kr channel activation (Table S3). APs were recorded in hiPSC-CMs that exhibited automatic activity (13). In cells infected with Tbx20 WT (n = 10), maximum diastolic potential and AP amplitude averaged −68.4 ± 1.9 and 98.7 ± 14.2 mV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…After transplantation, ideal ECT supposes to be paced by host heart. A recent study reported human iPS cell-derived CMs monolayer on biomatrix made of matrigel and PDMS are successively paced with different pacing frequencies from 0.7 Hz to 2.5 Hz [37]. In another report, the ECT composed with pig cECM and neonatal rat ventricular cells are response to different electrical stimulation from 1 to 5 Hz [10].…”
Section: Discussionmentioning
confidence: 99%